Developmental Trauma: The Effects and Signs of Traumatic Events on Children, and Its Implications - Vigh, Noémi (Social and Personality Development in Childhood, 2025)
Trauma is a concept that has grown so popular in the last years that sometimes it can be considered overused and losing its weight. However, it is still popular in self-help literature, common speech and does not seem to gain its rightful place among mental health or other professionals, despite its groundbreaking neuroscientific and evolutionary background. It would be important for professionals to understand the relevance of this framework and its scientific basis, use it in contexts where it can be relevant, and even bring long awaited reforms and changes. So ‘the baby should not be thrown out with the bathwater’, meaning that trauma should not be neglected, just because it has become “too fashionable”. In this chapter I will help to understand the basics and the relevance of this framework, focusing on developmental trauma that is revolutionary in our understanding of symptoms, dynamics and treatment of mental health issues affecting both children and adults. The whole developmental period of a human, and how it is affected by upbringing and other early age experiences has its implications for the rights and legal protection of children and childhood in general, thus it would be more than useful to obtain a common understanding among social, educational and legal professionals. Keywords: developmental trauma; PTSD; trauma informed education; trauma consciousness in legal systems; secondary traumatization